Quartz glass material and preparation method thereof
Through a high solids silica sol system and gradient damping calcining process, the large shrinkage and cracking problems of the sol-gel method are solved, and a high transmittance and low cost fine structure preparation is achieved.
Patent Information
- Application Number
- CN202510681984.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-09-02
AI Technical Summary
The existing sol-gel method for preparing quartz glass is prone to high shrinkage and structural defects, especially the cracking problem during material glue removal is difficult to effectively solve.
Quartz glass materials are prepared by controlling the ratio of silica nanopowder to water, adding an appropriate amount of dispersant, water-soluble monofunctional polymer monomer and initiator, combined with gradient humidity reduction and calcination processes.
It effectively avoids cracking and structural deformation of quartz glass, realizes one-time molding of fine surface structures, reduces processing costs, and improves the transmittance and purity of quartz glass.
Smart Images

Figure CN120573931A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of quartz glass preparation, and in particular to a quartz glass material and a preparation method thereof. Background Art
[0002] Quartz glass has excellent optical transmittance (ultraviolet-visible-infrared full band), low thermal expansion coefficient (5.5×10 -7 / ℃), high chemical stability and other characteristics, and is widely used in high-end optical devices, optical communication components, laser systems and microfluidic chips. The current mainstream preparation methods include: (1) high-temperature melting method, using high-purity quartz sand (SiO2 ≥ 99.99%) as raw material, heating it to above 2000℃ in an electric arc furnace or hydrogen-oxygen flame to melt it, and then cooling it into shape; (2) gas phase synthesis method, burning silicon precursors such as silicon tetrachloride in an oxygen-containing atmosphere to form silicon dioxide nanoparticles and deposit them on quartz glass; (3) sol-gel method: using silicon alkoxide as a precursor, hydrolysis-condensation to form a sol, which is then gelled, dried, and sintered into glass. Quartz glass prepared by high-temperature melting method is mainly processed through grinding and polishing processes. Fine structures are difficult to achieve through precision molding processes. Dry or wet etching, laser direct writing and other technologies are required for processing, which are difficult and costly. The equipment required for the gas phase synthesis method is complex, and it is difficult to prepare large-size or thick-walled products, which is costly. The properties of quartz glass prepared by sol-gel method are comparable to those of fused quartz, and the preparation conditions are relatively mild. Using molding molds, it can also be formed at near room temperature, and quartz glass products with specific structures (such as microlens arrays) can be prepared at low cost. Therefore, the preparation of precision quartz glass and products based on sol-gel method has cost advantages and application prospects.
[0003] However, the existing sol-gel method has problems such as low sol solid content, large drying shrinkage, and easy cracking of the product. Although the shrinkage rate has been partially improved by adding nano-vaporized silica or photocuring slurry in the existing technology, there are still defects such as excessively high organic matter content, large shrinkage, and high difficulty in process control. In particular, the cracking problem during the material debinding process is difficult to effectively solve. Summary of the Invention
[0004] The main purpose of this application is to provide a quartz glass material and a preparation method thereof, aiming to solve the technical problems of large shrinkage and structural defects in the existing sol-gel method for preparing quartz glass.
[0005] To achieve the above objectives, the present application proposes a method for preparing a quartz glass material, comprising the following steps: Mix water, silica nanopowder, dispersant, water-soluble monofunctional polymer monomer and initiator in proportion, and adjust the pH to obtain silica sol; wherein the volume ratio of the silica nanopowder to water is (0.4-0.9):1; The silica sol is injection molded, heated and gelled, and demolded to obtain a wet gel; At room temperature, gradually reducing the humidity to evaporate the water in the wet gel to obtain a silica xerogel; calcining the silica xerogel at 550° C. to 800° C. to remove binder, thereby obtaining a silica powder blank; The silicon dioxide powder blank is sintered at 1250° C. to 1400° C. to obtain a quartz glass material.
[0006] Optionally, the silica nanopowder is amorphous silica, the particle size of the silica nanopowder is 10nm-200nm, and the particle size of the silica nanopowder is preferably 20nm-80nm; the volume ratio of the silica nanopowder to water is (0.55-0.75):1, and the volume ratio of the silica nanopowder to water is preferably (0.6-0.7):1.
[0007] Optionally, the dispersant is one of a polymer dispersant, an organic small molecule dispersant or an inorganic dispersant; the polymer dispersant includes ammonium polyacrylate, polyacrylamide and polyepoxysuccinic acid; the organic small molecule dispersant includes ammonium citrate, ammonium succinate and ammonium benzenesulfonate; the inorganic dispersant includes ammonium dihydrogen phosphate and ammonium tripolyphosphate; the added amount of the dispersant is 0.1%-1.5% of the mass of the silica nanopowder, and preferably the added amount of the dispersant is 0.1%-1.0% of the mass of the silica nanopowder.
[0008] Optionally, the water-soluble monofunctional polymer monomer includes a mixture of one or more of methacrylic acid, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide and N-hydroxymethyl acrylamide; the added amount of the water-soluble monofunctional polymer monomer is 1%-25% of the mass of the silica nanopowder, preferably the added amount of the water-soluble monofunctional polymer monomer is 3%-15% of the mass of the silica nanopowder, and more preferably the added amount of the water-soluble monofunctional polymer monomer is 5%-10% of the mass of the silica nanopowder.
[0009] Optionally, the silica sol also includes a crosslinker, which is a water-soluble bifunctional polymer crosslinker, and the crosslinker includes a mixture of one or more of N,N'-methylenebisacrylamide, N,N'-methylenebismethylacrylamine, and ethylene glycol diacrylate; the added amount of the crosslinker is 0%-3% of the mass of the silica nanopowder, preferably the added amount of the crosslinker is 0%-1% of the mass of the silica nanopowder; the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.2):1, preferably the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.05):1.
[0010] Optionally, the initiator includes a mixture of one or more of ammonium persulfate, tert-butyl hydroperoxide, azobisisobutylamidine hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline hydrochloride; the added amount of the initiator is 0.1%-1% of the mass of the silica nanopowder, preferably the added amount of the initiator is 0.3%-0.6% of the mass of the silica nanopowder.
[0011] Optionally, in the step of heating and gelling the silica sol after injection molding, the heating temperature is 60° C.-80° C. and the holding time is 1 h-4 h.
[0012] Optionally, in the step of calcining the silica xerogel at 550° C.-800° C. for debinding, the heating rate is 0.1° C. / min-2° C. / min, and the calcination time is 1 h-5 h.
[0013] Optionally, in the step of sintering the silicon dioxide powder blank at 1250° C.-1400° C., the heating rate is 1° C. / min-10° C. / min, and the sintering time is 0.2 h-5 h.
[0014] The present application also proposes a quartz glass material obtained by the above-mentioned preparation method of the quartz glass material.
[0015] This application has at least the following beneficial effects: The present application uses a silica sol system with a high solid content and a low organic content to minimize sample size shrinkage during the process, effectively avoiding structural defects such as cracking and edge collapse of the quartz glass. Furthermore, the size shrinkage during the wet gel drying and sintering densification processes is isotropic, and the shrinkage rate is related to the silica solid content and organic content, effectively preventing structural deformation. Using an injection molding mold, the precise structure of the mold surface can be completely replicated, enabling the one-step molding of quartz glass optical components with a fine surface structure. This eliminates the need for subsequent post-processing steps such as laser etching and polishing, reducing processing costs. The SiO2 sol prepared in this application has the characteristics of low viscosity and high dispersibility, and internal bubbles are easily discharged. The prepared quartz glass has few micropores inside and can well fill the mold during injection molding. It is suitable for preparing various quartz glass products with complex surface structures. The raw materials used in this application are mainly water and silicon dioxide, and the amount of other additives (monomers, cross-linking agents, etc.) is reduced by 70%-80% compared with the traditional sol-gel method. After calcination, all additives are completely removed, and a high-purity SiO2 sintered green billet can be obtained. While effectively avoiding sample crystallization, it also achieves high transmittance of quartz glass in the ultraviolet-visible-near-infrared bands. In addition, the raw material cost is low and the impact on the environment is small, making it suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0017] Figure 1 This is a flow chart of the method for preparing the quartz glass material described in the embodiments of the present application; Figure 2 This is a test chart of the transmittance of the quartz glass material described in Example 1 of the present application in the ultraviolet-visible-infrared light region; Figure 3 Schematic diagram of the forming mold, wet gel and sintered microlens array quartz glass described in Example 5 of the present application.
[0018] The realization of the objectives, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0020] In view of the technical problems existing in the prior art, the embodiments of the present application provide a method for preparing a quartz glass material, such as Figure 1 As shown, the following steps are included: S10. Mix water, silica nanopowder, dispersant, water-soluble monofunctional polymer monomer and initiator in proportion, adjust the pH to the target value with hydrochloric acid, glacial acetic acid or concentrated ammonia water so that the dispersant has an optimal dispersing effect, and obtain silica sol; wherein the volume ratio of the silica nanopowder to water is (0.4-0.9):1.
[0021] Specifically, the silica nanopowder is amorphous silica, with a particle size of 10nm-200nm. Amorphous nanoparticles have high surface activity and, when combined with a dispersant (such as ammonium polyacrylate), can form a stable sol, preventing agglomeration. Nanoscale silica (preferably with a particle size of 20nm-80nm) provides a high specific surface area, promoting particle rearrangement and densification during the sintering phase, thereby increasing the density of the quartz glass. Furthermore, amorphous silica can prevent grain boundary scattering, thereby improving the transmittance of the quartz glass in the ultraviolet-visible-infrared region.
[0022] The volume ratio of the silica nanopowder to water is preferably (0.55-0.75):1, and more preferably, the volume ratio of the silica nanopowder to water is (0.6-0.7):1. By controlling the silica solid content in the silica sol to 0.6-0.7, the shrinkage of the gel during the drying and sintering stages can be reduced, avoiding cracking and structural deformation of the quartz glass product. The preferred volume ratio of (0.6-0.7):1 ensures a high solid content while maintaining a low viscosity of the sol, ensuring the fluidity of the sol and facilitating the filling of mold microstructures (such as a microlens array with an aspect ratio of ≥5:1).
[0023] The water-soluble monofunctional polymer monomer includes a mixture of one or more of methacrylic acid, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide and N-hydroxymethyl acrylamide; the added amount of the water-soluble monofunctional polymer monomer is 1%-25% of the mass of the silica nanopowder, preferably, the added amount of the water-soluble monofunctional polymer monomer is 3%-15% of the mass of the silica nanopowder, and more preferably, the added amount of the water-soluble monofunctional polymer monomer is 5%-10% of the mass of the silica nanopowder.
[0024] The silica sol also includes a crosslinker, which is a water-soluble bifunctional polymer crosslinker, and the crosslinker includes a mixture of one or more of N,N'-methylenebisacrylamide, N,N'-methylenebismethylacrylamine, and ethylene glycol diacrylate; the added amount of the crosslinker is 0%-3% of the mass of the silica nanopowder, preferably, the added amount of the crosslinker is 0%-1% of the mass of the silica nanopowder; the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.2):1, preferably, the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.05):1.
[0025] In the present application, the water-soluble monofunctional polymer monomer and the water-soluble bifunctional polymer cross-linker work together to form a three-dimensional network structure, thereby increasing the elastic modulus of the wet gel and avoiding the risk of cracking during demolding. By precisely controlling the amount of cross-linker used, the residual carbon content after calcination can be reduced, thereby avoiding the blackening of the quartz glass and poor transmittance.
[0026] The initiator comprises a mixture of one or more of ammonium persulfate, tert-butyl hydroperoxide, azobisisobutylamidine hydrochloride, azobiscyanovaleric acid, and azobisisopropylimidazoline hydrochloride. The initiator is added in an amount of 0.1% to 1% by weight of the silica nanopowder, preferably 0.3% to 0.6% by weight. The initiator efficiently decomposes free radicals at temperatures between 60°C and 80°C, shortening the polymerization time to 1 to 4 hours. The initiator also completely decomposes (e.g., SO₃ gas is generated and escapes upon calcination of ammonium persulfate), preventing residual metal ions from affecting the purity of the quartz glass.
[0027] The dispersant is one of a polymer dispersant, an organic small molecule dispersant or an inorganic dispersant; the polymer dispersant includes ammonium polyacrylate, polyacrylamide and polyepoxysuccinic acid; the organic small molecule dispersant includes ammonium citrate, ammonium succinate and ammonium benzenesulfonate; the inorganic dispersant includes ammonium dihydrogen phosphate and ammonium tripolyphosphate; the amount of the dispersant added is 0.1%-1.5% of the mass of the silica nanopowder, preferably, the amount of the dispersant added is 0.1%-1.0% of the mass of the silica nanopowder, The preferred content and the most suitable pH value of the powder are related to the type of dispersant. For example, if ammonium polyacrylate is used as the dispersant, the added amount of the dispersant is preferably 0.2%-0.6% of the mass of the silica nanopowder, and the pH value range for better dispersion effect is 3.5-5; if ammonium citrate is used as the dispersant, the added amount of the dispersant is preferably 0.1%-0.8% of the mass of the silica nanopowder, more preferably, the added amount of the dispersant is 0.1%-0.5% of the mass of the silica nanopowder, and the pH value range for better dispersion effect is 10-12.
[0028] The present application effectively increases the solid content of SiO2 and significantly reduces the organic matter content in the SiO2 sol by introducing an appropriate amount of dispersant and avoiding the introduction of large molecular weight plasticizers, pH adjusters, or other additives such as gelling agents, except for necessary small molecular weight monomers and cross-linking agents. The silica nanopowder dispersed in a unit volume of pure water is 0.4-0.9 times the volume of water, while ensuring good dispersibility of the SiO2 sol. The prepared SiO2 sol has low viscosity, high solid content, good stability, and is easy to fill into a molding mold. This facilitates the one-step injection molding of quartz glass products with a fine surface structure without the need for subsequent processing, thereby enabling the low-cost preparation of various quartz glass products with complex surface structures.
[0029] S20, after injection molding the silica sol, heating and gelling, the heating temperature is 60-80° C., the heat preservation time is 1-4 hours, and after demolding, a wet gel is obtained.
[0030] Specifically, a molding mold can be selected according to the various types of quartz glass products with fine surface structures to be prepared. By heating at 60°C-80°C to initiate the polymerization reaction of polymer monomers and cross-linking agents, the dispersibility of the sol system can be improved, rapid gel curing is achieved, and the gelation time is greatly shortened. The sample has almost no dimensional shrinkage during the gelation process, and due to the bonding effect of the polymer, the wet gel has a high strength, which can effectively prevent the wet gel from cracking and enable it to be completely demolded. At the same time, since the injection molding mold has mild operating conditions and can be reused many times, the production cost of the mold is effectively reduced.
[0031] S30. At room temperature, gradually reducing the humidity to evaporate the water in the wet gel to obtain a silica dry gel.
[0032] The present application uses gradient dehumidification to evaporate the moisture inside the wet gel, maintains the temperature near room temperature, and controls the ambient humidity to gradually decrease (for example, from 90% RH to 50% RH). The moisture inside the wet gel is slowly evaporated, which promotes the close packing of silica powder, avoids large pore defects, and improves the density of subsequent sintering. The slow evaporation avoids rapid water loss and cracking on the surface of the wet gel, allowing the internal moisture to slowly and evenly migrate to the surface, reducing the internal stress caused by the difference in drying rates inside and outside, and providing time for stress release in the gel network, preventing the expansion of microcracks caused by sudden water loss. In addition, due to the increased SiO2 solid content in the present application, the dimensional shrinkage of the wet gel during the drying process is effectively reduced, and sample cracking is further avoided through controlled drying, which is conducive to the preparation of high-quality quartz glass products.
[0033] For wet gels with micron-scale structures (such as microlens arrays), gradient dehumidification drying can avoid the collapse or deformation of the surface structure, thereby meeting the high-precision requirements of optical components.
[0034] S40, calcining the silica xerogel at 550° C.-800° C. to remove binder, thereby obtaining a silica powder blank.
[0035] In the specific implementation process, the silica dry gel is calcined in air with a heating rate of 0.1°C / min-2°C / min and a calcination time of 1h-5h. The sample is relatively thick, so a lower heating rate should be selected to completely oxidize and decompose the organic matter inside it. After calcination, the introduced solvent and all additives can be completely removed to obtain a well-formed high-purity SiO2 powder blank, which is conducive to the preparation of high-purity, non-crystallized, and highly transparent quartz glass.
[0036] S50, sintering the silica powder blank at 1250° C.-1400° C. with a heating rate of 1° C. / min-10° C. / min and a sintering time of 0.2 h-5 h to obtain a quartz glass material.
[0037] After sintering, the powder can be densified and the final density is close to the theoretical value (2.20g / cm 3 ) quartz glass material, and it is sintered at 1250℃-1400℃, which significantly reduces energy consumption compared to traditional high-temperature melting process (>2000℃).
[0038] The embodiments of the present application further provide a quartz glass material obtained by the above-mentioned preparation method of the quartz glass material.
[0039] The above technical solutions of the present application are described in detail below with reference to specific embodiments.
[0040] Example 1 A method for preparing a quartz glass material comprises the following steps: 1) The designed ratio of silica sol is: Silica nanopowder (amorphous, particle size D50 = 50nm, purity ≥ 99.99%, specific surface area 200m 2 / g), SiO2 solid content is 0.55 (volume ratio, that is, 0.55L SiO2 powder is dispersed in 1L water, corresponding to a mass ratio of 1.32:1); Acrylamide monomer, content is 4wt% (accounting for the mass of SiO2); Cross-linking agent N,N'-methylenebisacrylamide, content of 0.2wt% (based on the mass of SiO2); Dispersant ammonium polyacrylate, content 0.4wt% (based on SiO2 mass); Initiator ammonium persulfate, content 0.2wt% (based on SiO2 mass); Ultrapure water is the balance; The acrylamide monomer, N,N'-methylenebisacrylamide and ammonium polyacrylate in the above ratio were dissolved in ultrapure water and magnetically stirred at 500 rpm for 10 minutes. Glacial acetic acid was then added dropwise to adjust the pH to 3.5±0.1 (calibrated by a pH meter). SiO2 powder was then added in 5 batches with an interval of 5 minutes between each batch. The stirring speed was increased to 2000 rpm and the stirring was continued for 0.5 hours to prevent agglomeration. Ammonium persulfate was then added and the stirring was continued for 5 minutes to dissolve and disperse the powder evenly. The mixture was then centrifuged to remove bubbles to obtain a silica sol with good dispersion.
[0041] 2) Injection molding and gelation: The prepared silica sol was injected into a polytetrafluoroethylene mold, covered, and kept in a constant temperature oven at 70°C for 1.5 hours to complete gelation. After cooling to room temperature, the mold was removed to obtain a wet gel.
[0042] 3) Drying of wet gel: Drying is carried out using a gradient controlled humidity method: Stage 1: 25°C, 90% RH (humidity chamber controlled), maintain for 12 hours; Phase 2: Reduce humidity by 10% RH every 12 hours, ending at 50% RH, and maintain for 24 hours; After drying, silica xerogel was obtained, with a linear shrinkage of 8% (volume shrinkage ≈ 24%).
[0043] 4) Calcination and debinding: The silica dry gel was heated to 620°C at a rate of 1°C / min, kept at this temperature for 4 hours, and then naturally cooled to room temperature to obtain a silica powder blank.
[0044] 5) Sintering densification: The silica powder blank was heated to 1300° C. at a rate of 5° C. / min, kept at this temperature and sintered for 2 hours, and then cooled in the furnace to obtain a quartz glass material.
[0045] Performance testing: According to the method specified in GB / T7962.20-1987, the density of the quartz glass material prepared in this embodiment was tested and the density of the quartz glass material was found to be 2.20 g / cm 3 , which is consistent with the theoretical density of quartz glass; According to the method specified in GB / T 7962.1-2010, the refractive index n of the quartz glass material prepared in this embodiment was tested. d , the refractive index n of the quartz glass material is measured d It is 1.45838, which is comparable to fused quartz; The transmittance of the quartz glass material prepared in this embodiment in the ultraviolet-visible-infrared region was tested, and the test results are as follows: Figure 2 As shown, its transmittance is ≥92%, indicating that the quartz glass material has a high transmittance in the ultraviolet-visible-infrared light region.
[0046] Example 2 A method for preparing a quartz glass material comprises the following steps: 1) The designed ratio of silica sol is: Silica nanopowder (amorphous, particle size D50 = 50nm, purity ≥ 99.99%, specific surface area 200m 2 / g), SiO2 solid content is 0.7 (volume ratio, i.e. 0.7L SiO2 powder is dispersed in 1L water); 4-Hydroxybutyl acrylate monomer, content of 6wt% (based on the mass of SiO2); Cross-linking agent N,N'-methylenebisacrylamide, content of 0.2wt% (based on the mass of SiO2); Dispersant ammonium citrate, content 0.3wt% (based on SiO2 mass); Initiator: azobisisobutylamidine hydrochloride, content: 0.4wt% (based on SiO2 mass); Ultrapure water is the balance; The 4-hydroxybutyl acrylate monomer, N,N'-methylenebisacrylamide and ammonium citrate in the above-mentioned proportion were dissolved in ultrapure water and magnetically stirred at a speed of 500 rpm for 10 minutes. Then, concentrated ammonia water was added dropwise to adjust the pH to 11.5±0.1 (calibrated by a pH meter). Then, SiO2 powder was added in 5 batches, with an interval of 10 minutes between each batch. At the same time, the stirring speed was increased to 2000 rpm, and the stirring was continued for 1 hour to prevent agglomeration. Then, azobisisobutylamidine hydrochloride was added and stirring was continued for 5 minutes to dissolve and disperse it evenly. After that, centrifugation was performed to remove bubbles to obtain a silica sol with good dispersion.
[0047] 2) Injection molding and gelation: The prepared silica sol was injected into a polypropylene plastic watch glass mold, covered, and kept in a constant temperature oven at 75°C for 1 hour to complete gelation. After cooling to room temperature, the mold was removed to obtain a wet gel.
[0048] 3) Drying of wet gel: Drying is carried out using a gradient humidity control method: Stage 1: 20°C, 95% RH (humidity chamber controlled), maintain for 5 hours; Phase 2: Reduce humidity by 5% RH every 5 hours until reaching 50% RH, maintaining for 36 hours; After drying, silica xerogel was obtained.
[0049] 4) Calcination and debinding: The silica dry gel was heated to 700°C at a rate of 0.5°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to obtain a silica powder blank.
[0050] 5) Sintering densification: The silica powder blank was heated to 1380° C. at a rate of 8° C. / min, sintered at this temperature for 0.5 h, and then cooled in the furnace to obtain a quartz glass material.
[0051] Example 3 A method for preparing a quartz glass material comprises the following steps: 1) The designed ratio of silica sol is: Silica nanopowder (amorphous, particle size D50 = 50nm, purity ≥ 99.99%, specific surface area 200m 2 / g), SiO2 solid content is 0.6 (volume ratio, i.e. 0.6L SiO2 powder is dispersed in 1L water); Hydroxyethyl acrylate monomer, content of 12wt% (based on the mass of SiO2); Cross-linking agent ethylene glycol diacrylate, content 0.1wt% (based on SiO2 mass); Dispersant ammonium tripolyphosphate, content 0.2wt% (based on SiO2 mass); Initiator tert-butyl hydroperoxide, content 0.3wt% (based on SiO2 mass); Ultrapure water is the balance; The hydroxyethyl acrylate monomer, ethylene glycol diacrylate and ammonium tripolyphosphate in the above ratio were dissolved in ultrapure water and magnetically stirred at 500 rpm for 10 minutes. Then, concentrated ammonia water was added dropwise to adjust the pH to 8±0.1 (calibrated by pH meter). Then, SiO2 powder was added in 5 batches with an interval of 5 minutes between each batch. At the same time, the stirring speed was increased to 2000 rpm and the stirring was continued for 0.5 hours to prevent agglomeration. Then, tert-butyl hydroperoxide was added and the stirring was continued for 10 minutes to dissolve and disperse it evenly. Then, the mixture was centrifuged to remove bubbles to obtain a silica sol with good dispersion.
[0052] 2) Injection molding and gelation: The prepared silica sol was injected into a polyethylene plastic mold, covered, and kept in a constant temperature oven at 65°C for 3 hours to complete gelation. After cooling to room temperature, the mold was removed to obtain a wet gel.
[0053] 3) Drying of wet gel: Drying is carried out using a gradient humidity control method: Stage 1: 23°C, 95% RH (humidity chamber controlled), maintain for 8 hours; Phase 2: Reduce humidity by 5% RH every 8 hours, ending at 50% RH, and maintain for 48 hours; After drying, silica xerogel was obtained.
[0054] 4) Calcination and debinding: The silica dry gel was heated to 750°C at a rate of 0.5°C / min, kept at this temperature for 1.5 hours, and then cooled to room temperature naturally to obtain a silica powder blank.
[0055] 5) Sintering densification: The silica powder blank was heated to 1350°C at a rate of 6°C / min, sintered at this temperature for 1 hour, and then cooled in the furnace to obtain a quartz glass material.
[0056] Example 4 A method for preparing a quartz glass material comprises the following steps: 1) The designed ratio of silica sol is: Silica nanopowder (amorphous, particle size D50 = 50nm, purity ≥ 99.99%, specific surface area 200m 2 / g), SiO2 solid content is 0.7 (volume ratio, i.e. 0.7L SiO2 powder is dispersed in 1L water); Hydroxyethyl methacrylate monomer, content of 8wt% (based on the mass of SiO2); Cross-linking agent N,N'-methylenebis(methylpropyleneamine), content of 0.16wt% (based on SiO2 mass); Dispersant ammonium succinate, content 0.5wt% (based on SiO2 mass); Initiator: azobis(cyano)valeric acid, content: 0.4wt% (based on SiO2 mass); Ultrapure water is the balance; The above-mentioned proportion of hydroxyethyl methacrylate monomer, N,N'-methylenebis(methyl)acrylamine and ammonium succinate was dissolved in ultrapure water and magnetically stirred at 500 rpm for 10 minutes. Then, concentrated ammonia water was added dropwise to adjust the pH to 11±0.1 (calibrated by pH meter). Then, SiO2 powder was added in 5 batches with an interval of 5 minutes between each batch. At the same time, the stirring speed was increased to 2000 rpm and the stirring was continued for 1 hour to prevent agglomeration. Then, azobis(cyano)pentanoic acid was added and stirring was continued for 5 minutes to dissolve and disperse it evenly. Then, the mixture was centrifuged to remove bubbles to obtain a silica sol with good dispersion.
[0057] 2) Injection molding and gelation: The prepared silica sol was injected into a polytetrafluoroethylene mold, covered, and kept in a constant temperature oven at 75°C for 2 hours to complete gelation. After cooling to room temperature, the mold was removed to obtain a wet gel.
[0058] 3) Drying of wet gel: Drying is carried out using a gradient humidity control method: Stage 1: 20°C, 90% RH (humidity chamber controlled), maintain for 12 hours; Phase 2: Reduce humidity by 8% RH every 12 hours, ending at 50% RH, and maintain for 24 hours; After drying, silica xerogel was obtained.
[0059] 4) Calcination and debinding: The silica dry gel was heated to 600°C at a rate of 0.8°C / min, kept at this temperature for 3 hours, and then naturally cooled to room temperature to obtain a silica powder blank.
[0060] 5) Sintering densification: The silica powder blank was heated to 1050°C at a rate of 10°C / min, kept warm and sintered for 2 hours, then heated to 1320°C at a rate of 6°C / min, kept warm and sintered for 0.2 hours, and cooled in the furnace to obtain a quartz glass material.
[0061] Example 5 A method for preparing quartz glass having an array lens on its surface comprises the following steps: 1) The designed ratio of silica sol is: Silica nanopowder (amorphous, particle size D50 = 50nm, purity ≥ 99.99%, specific surface area 200m 2 / g), SiO2 solid content is 0.62 (volume ratio, i.e. 0.62L SiO2 powder is dispersed in 1L water); N-hydroxymethyl acrylamide monomer, content of 10wt% (based on the mass of SiO2); Cross-linking agent N,N'-methylenebis(methylpropyleneamine), content of 0.16wt% (based on SiO2 mass); Dispersant ammonium benzenesulfonate, content is 0.5wt% (based on SiO2 mass); Initiator: azobisisopropylimidazoline hydrochloride, content: 0.3wt% (based on SiO2 mass); Ultrapure water is the balance; The N-hydroxymethyl acrylamide monomer, N,N'-methylenebis(methyl)acrylamide and ammonium benzenesulfonate in the above-mentioned proportion were dissolved in ultrapure water and magnetically stirred at a speed of 500 rpm for 10 minutes. Then, concentrated ammonia water was added dropwise to adjust the pH to 7±0.1 (calibrated by pH meter). Then, SiO2 powder was added in 5 batches with an interval of 5 minutes between each batch. At the same time, the stirring speed was increased to 2000 rpm and the stirring was continued for 1 hour to prevent agglomeration. Then, azobis(isopropyl)imidazoline hydrochloride was added and the stirring was continued for 5 minutes to dissolve and disperse it evenly. Then, the mixture was centrifuged to remove bubbles to obtain a silica sol with good dispersion.
[0062] 2) Injection molding and gelation: Mold design: Silicone rubber (PDMS, hardness Shore A 50) was used to fabricate a convex microlens array (unit spherical radius 3.00, height difference between center and edge <0.02mm, ineffective area (ridge) width ≤4μm) by photolithography-replication method. Figure 3 As shown; The prepared silica sol was injected into the silicone rubber mold with the surface array structure, sealed, and kept in a constant temperature oven at 75°C for 2 hours to complete the gelation. After cooling naturally to room temperature, the mold was removed to obtain a wet gel with a surface structure, such as Figure 3 shown.
[0063] 3) Drying of wet gel: Drying is carried out using a gradient humidity control method: Stage 1: 25°C, 95% RH (humidity chamber controlled), maintain for 12 hours; Phase 2: Reduce humidity by 5% RH every 12 hours, ending at 50% RH, and maintain for 48 hours; After drying, silica xerogel was obtained.
[0064] 4) Calcination and debinding: The silica dry gel was heated to 650°C at a rate of 0.5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature naturally to obtain a silica powder blank.
[0065] 5) Sintering densification: The silica powder blank was heated to 1020℃ at a rate of 5℃ / min, kept warm and sintered for 3h, then heated to 1350℃ at a rate of 3℃ / min, kept warm and sintered for 1h, and cooled in the furnace to obtain a quartz glass product with an array lens on the surface, such as Figure 3 shown.
[0066] The above are merely optional embodiments of the present application and do not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification and drawings under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.
Claims
1. A method for preparing a quartz glass material, characterized in that: The following steps are involved: Mix water, silica nanopowder, dispersant, water-soluble monofunctional polymer monomer and initiator in proportion, and adjust the pH to obtain silica sol; wherein the volume ratio of the silica nanopowder to water is (0.4-0.9):1; The silica sol is injection molded, heated and gelled, and demolded to obtain a wet gel; At room temperature, gradually reducing the humidity to evaporate the water in the wet gel to obtain a silica xerogel; calcining the silica xerogel at 550° C. to 800° C. to remove binder, thereby obtaining a silica powder blank; The silicon dioxide powder blank is sintered at 1250° C. to 1400° C. to obtain a quartz glass material.
2. The method for preparing the quartz glass material according to claim 1, wherein: The silica nanopowder is amorphous silica, and the particle size of the silica nanopowder is 10nm-200nm, and the particle size of the silica nanopowder is preferably 20nm-80nm; the volume ratio of the silica nanopowder to water is (0.55-0.75):1, and the volume ratio of the silica nanopowder to water is preferably (0.6-0.7):
1.
3. The method for preparing the quartz glass material according to claim 1, wherein: The dispersant is one of a polymer dispersant, an organic small molecule dispersant or an inorganic dispersant; the polymer dispersant includes ammonium polyacrylate, polyacrylamide and polyepoxysuccinic acid; the organic small molecule dispersant includes ammonium citrate, ammonium succinate and ammonium benzenesulfonate; the inorganic dispersant includes ammonium dihydrogen phosphate and ammonium tripolyphosphate; the added amount of the dispersant is 0.1%-1.5% of the mass of the silica nanopowder, and preferably the added amount of the dispersant is 0.1%-1.0% of the mass of the silica nanopowder.
4. The method for preparing the quartz glass material according to claim 1, wherein: The water-soluble monofunctional polymer monomer includes a mixture of one or more of methacrylic acid, 4-hydroxybutyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, acrylamide and N-hydroxymethyl acrylamide; the added amount of the water-soluble monofunctional polymer monomer is 1%-25% of the mass of the silica nanopowder, preferably the added amount of the water-soluble monofunctional polymer monomer is 3%-15% of the mass of the silica nanopowder, and more preferably the added amount of the water-soluble monofunctional polymer monomer is 5%-10% of the mass of the silica nanopowder.
5. The method for preparing the quartz glass material according to claim 1, wherein: The silica sol also includes a crosslinker, which is a water-soluble bifunctional polymer crosslinker, and the crosslinker includes a mixture of one or more of N,N'-methylenebisacrylamide, N,N'-methylenebismethylacrylamine, and ethylene glycol diacrylate; the added amount of the crosslinker is 0%-3% of the mass of the silica nanopowder, preferably 0%-1% of the mass of the silica nanopowder; the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.2):1, preferably the mass ratio of the crosslinker to the water-soluble monofunctional polymer monomer is (0-0.05):
1.
6. The method for preparing the quartz glass material according to claim 1, wherein: The initiator comprises a mixture of one or more of ammonium persulfate, tert-butyl hydroperoxide, azobisisobutylamidine hydrochloride, azobiscyanovaleric acid and azobisisopropylimidazoline hydrochloride; the added amount of the initiator is 0.1%-1% of the mass of the silicon dioxide nanopowder, preferably 0.3%-0.6% of the mass of the silicon dioxide nanopowder.
7. The method for preparing the quartz glass material according to claim 1, wherein: After the silica sol is injected into a mold, in the step of heating and gelling, the heating temperature is 60° C.-80° C. and the heat preservation time is 1 hour-4 hours.
8. The method for preparing a quartz glass material according to claim 1, wherein: In the step of calcining the silica xerogel at 550° C.-800° C. for debinding, the heating rate is 0.1° C. / min-2° C. / min, and the calcination time is 1 h-5 h.
9. The method for preparing a quartz glass material according to claim 1, wherein: In the step of sintering the silicon dioxide powder blank at 1250° C.-1400° C., the heating rate is 1° C. / min-10° C. / min, and the sintering time is 0.2 h-5 h.
10. A quartz glass material, characterized in that: Obtained by the preparation method of the quartz glass material according to any one of claims 1 to 9.